The study on tone and manner of advertising for anti-dengue campaign in press ad / Norsharina Samsuri - Samsuri, Norsharina (2012)
Recently in Malaysia, the statistics of dengue fever cases and death rates due to viral infection from Andes mosquitoes increase every year. The press release by Director General of Health Malaysia, Tan Sri Dato' Seri Dr. Haji Mohd Ismail Merican (2010) reported that the cumulative number of dengue fever cases in the report until week 46 in 2009 was 36.514. It has increased by 15% in week 46 for the year of 2010 with a total of 42.914 cases. Meanwhile, the death rate in week 46 in 2009 amounted to 78 cases. Then, it increases by 62% in week 46 for the year of 2010 with the a total death of 125 people, putting Selangor as the largest contributor of casualties from dengue fever with 43 people dead from the year of 2009 until 2010. The Ministry of Health Department had put in a lot of effort to increase awareness and knowledge on the dangers of the Aedes mosquitoes and dengue fever, but the public does not care and less participated in efforts to eliminate and reduce the cases of dengue fever. This issue is highlighted in the newspaper headline: "Dengue cases up, so clean up and wipe out Aedes" which was reported by Annie Freeda Cruez 2010. The purpose of the study is to determine an appropriate approach in presenting information such as numbers, graph or statistics into this campaign using the right tone of advertising approach. This research analyzes all types of info graphic, studies the characteristic of each type and then identifies the best approach to present the information or the cases of dengue into this campaign. The info graphic in visualizing statistical data is to be applied in the anti-dengue campaign on print advertisement; this study highlights a few theories that can be used as a guideline to develop a creative objective.